Evaluating the Efficiency of Video Transmission Using a New Circular Search Algorithm Based on the Motion Estimation for a Single User (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The successful transmission of video over wireless networks faces many challenges and problems that contribute to the weakening of efficient transmission systems because of the limited resources and the environment surrounding the wireless signal. Therefore, In order to deal with these challenges we need not only to compress the video in efficient ways but also to use a good transmission system that overcome the errors of the channel and correct potential errors during the transmission process. In this paper, the transmission system depends on the transmission of the video to a single user, a proposed system to simulate the transmission in the mobile networks and to measure the efficiency of the transmission system is added to the percentage of noise (i.e. additive white Gaussian Noise (AWGN) channels). In many such practical systems, jointly source and channel coding the efficiency and performance of the transmission system can be greatly improved to obtain a transmission system without channel errors. The source coding decreases the redundancy in the signal sent to provide bandwidth and the channel/convolutional coding (CC) adds useful redundancy to combat channel errors. The circular search algorithm for motion estimation (ME) is used as a source coding method. The results show that the suggested system can produce a balance among the compression performance and maintain video quality. The methods used in the transmission process showed a great advantage in the performance of the channel encoding compared to that of another transmission system without channel coding.